2021
DOI: 10.1021/acs.nanolett.0c04946
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Transport of the 2D Surface State in a Nonsymmorphic Semimetal

Abstract: In a topological semimetal with Dirac or Weyl points, the bulk-boundary correspondence principle predicts a gapless edge mode if the essential symmetry is still preserved at the surface. The detection of such topological surface state has been considered as the fingerprint prove for crystals with nontrivial topological bulk band. On the contrary, it has been proposed that even with symmetry broken at the surface, a new surface band can emerge in nonsymmorphic topological semimetals. The symmetry reduction at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
(188 reference statements)
1
14
0
Order By: Relevance
“…Most of the WHM compounds are reported to be Dirac nodal line semimetals [11][12][13][14][15][16][17] or weak topological insulators [10,18]. However when W are Lanthanides with f electrons, magnetic orderings and Kondo effect could play a role in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the WHM compounds are reported to be Dirac nodal line semimetals [11][12][13][14][15][16][17] or weak topological insulators [10,18]. However when W are Lanthanides with f electrons, magnetic orderings and Kondo effect could play a role in the system.…”
Section: Introductionmentioning
confidence: 99%
“…15 It hosts a nonsymmorphic symmetryprotected type of Dirac state, and the Dirac bands are linearly dispersed (a large energy range of up to 2eV), which is larger than that of other known nodal-line semimetals. 16 ZrSiS has some exotic properties, such as an unusual surface floating band, robust transport, 17,18 and electronic correlation enhance-ment. 19,20 These characteristics are also expected in the isostructural compounds ZrSiSe and ZrSiTe.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast to SrAs 3 , the PbTaSe 2 -family and ZrSiS-type compounds belong to van der Waals materials, which provides an advantage in studying 2D surface states through suppressing bulk contributions in exfoliated nanoflakes. Recently, Liu et al have successfully probed an additional 2D quantum oscillation in confinement ZrSiSe thin flakes . But further analysis demonstrated that the surface states result from the trivial floating surface band due to the symmetry reduction rather than the topologically nontrivial drumhead surface state.…”
mentioning
confidence: 99%
“…The most common way to detect the surface state is to explore the 2D character of the angular dependent Shubnikov–de Haas (SdH) quantum oscillations of the surface state, , but it faces great challenges due to the influence of the bulk states. In order to enhance the surface SdH signal, the most efficient way is to enhance the surface to the bulk ratio by decreasing the thickness of a nanoflake or to shift the Fermi level into the bulk band gap by elemental doping or electric gating. , …”
mentioning
confidence: 99%
See 1 more Smart Citation